Investigation of bovine haemoplasmas and their association with anaemia in New Zealand cattle. Issue 1 (2nd January 2016) - McFadden, AMJ; Ha, HJ; Donald, JJ; Bueno, IM; van Andel, M; Thompson, JC; Tisdall, DJ; Pulford, DJ
Abstract: CASE HISTORY AND CLINICAL FINDINGS: A dairy cow, from a herd in the Waikato region of New Zealand, was reported with regenerative anaemia on 12 September 2014. Testing of blood from the animal using PCR assays for Theileria orientalis produced a negative result for both Chitose and Ikeda types. LABORATORY FINDINGS: Using PCR and DNA sequencing, blood from the cow was positive for Candidatus Mycoplasma haemobos. Further testing of another 12 animals from the case herd, 27 days after the affected cow was first reported, showed 11 animals were positive for Candidatus M. haemobos or Mycoplasma wenyonii in the PCR. None of these cattle were clinically anaemic or positive for T. orientalis Ikeda type using PCR. A convenience sample of 47 blood samples from cattle throughout New Zealand, submitted to the Investigation and Diagnostic Centre (Ministry for Primary Industries) for surveillance testing for T. orientalis Ikeda, was selected for further testing for bovine haemoplasmas. Of these samples, 6/47 (13%) and 13/47(28%) were positive for M. wenyonii and Candidatus M. haemobos, respectively. There was no difference in the proportion of samples positive for the bovine haemaplasmas between cattle with anaemia that were negative for T. orientalis (6/20, 33%), or without anaemia or T. orientalis (10/18, 56%), or from cattle herds experiencing anaemia and infection with T. orientalis Ikeda type (3/9, 33%). DIAGNOSIS: Bovine haemoplasmosis. CLINICAL RELEVANCE: The presence of bovine haemoplasmas in blood does not establish causality for anaemia in cattle. Diagnosis of anaemia associated with haemoplasmosis would require exclusion of other causes of regenerative anaemia and an association of the agent with anaemia in affected cattle herds. The data collected in this study did not provide evidence that bovine haemoplasmas were associated with a large number of outbreaks of anaemia in cattle in New Zealand.